Technical Perspective: Patching Program errors. - Rinard, Martin C. (Communications of the ACM, 2008)
The article discusses another article in this issues which examines efforts of computer scientists to patch, or fix, errors in computer programs. A technique for automatically isolating and correcting such errors is presented. Topics include computer programmers who use the C program that are familiar with out-of-bounds memory errors, randomly allocating blocks of memory larger than needed to execute a program, and the immediate generation of a patch without human interaction. Also discussed are programs that continue to operate in the face of errors.